Study of the Severity of COVID-19 Infection in Patients with Chronic Diseases - Alhamadani, Yousif; Hassan, Rima (Journal of Biomedicine and Biochemistry, 2022)
The object of study was conducted on 100 patients for both gender from three different geographical areas of Al-Muthanna Governorate, Samawah city, Al-Rumaitha district, and Al-Khader. The aim of the research was to study the association of chronic diseases with Covid- 19 disease. The strongest correlation of samples infected with Covid- 19 was found with the medical history of people with one or more diseases. Ages ranges were between 14 to over 60 years old. The study showed the following results: By age group of chronically ill patients 14-25 years old 2%, From 26-40 years 12%, 41-60 years old 18%, Over 60 years old 14%. By age group of healthy subjects14-25 years 12%, From 26-40 years 38%, 41-60 years old 9%, Over 60 years old 2%. According to the medical history, those with one or more chronic diseases were infected with the virus 44%, Healthy people were infected with the virus 56%. According to vaccination: The rate of infection of the vaccinated is 22%, The unvaccinated infection rate is 78%. The severity of infection among the vaccinated was16% mi- nor injury, 6% moderate injury. The incidence of people with chronic diseases and the severity of their infection, blood pressure diseases 6% minor injury, 12% moderate injury, 3% severe injury Diabetes: 3% minor injury, 5% moderate injury, 5% severe injury. heart disease: 2% moderate injury. Asthma diseases: 2% moderate injury. Correlation rate between chronic illness and infection with the Corona virus 3% have moderate incidence of hypertension and diabetes 4% have se- vere high blood pressure and diabetes.